Critical roles for c-Myb in lymphoid priming and early B-cell development - Greig, Kylie T. (American Society of Hematology, 2010)
c-Myb is a transcription factor with functions in many hematopoietic lineages. c-Myb–deficient mice display reduced numbers of B cells; however, it is unknown what role c-Myb plays in B lymphopoiesis because no critical target genes have been identified in the B-cell lineage. We demonstrate that conditional deletion of c-Myb in B-cell progenitors completely abolishes B-cell development. c-Myb is required for lymphoid progenitors to respond to the cytokines interleukin-7 and thymic stromal lymphopoietin; in the absence of sufficient c-Myb activity, mice display a B lymphopenia that closely resembles that observed in interleukin-7 receptor α–deficient animals. Analysis of the multipotent progenitor compartment indicates that c-Myb is also required for up-regulation of multiple lymphoid-associated genes, including Il7r, and for the subsequent development of the common lymphoid progenitor population. These data show that c-Myb plays a critical role in the regulatory pathways governing lymphoid specification and early B-cell differentiation.